Financial Ratio Analysis Of Primkoppol (Primer Koperasi POLRI) At Polres Of South Bengkulu - Alfarisy, Abdurrahman; Soleh, Ahmad; Rahman Febliansa, Muhammad (Journal of Law, Social Science, and Management Review, 2024)
This study aims to determine the financial conditions and developments of Primkoppol at Polres of South Bengkulu in 2015-2020 by using the ratio of liquidity, solvency, and profitability. This research was conducted in the form of a case study at Primkoppol at Polres of South Bengkulu. Data collection techniques used were documentation and interviews. The data analysis technique was used to calculate the ratios of liquidity, solvency, and profitability. The results of the research show the level of liquidity measured using the current ratio and quick ratio in 2015-2020 was categorized as quite good. The level of solvency measured using the total debt to equity ratio and the total debt to total assets ratio in 2015-2020 was categorized as quite good. The level of profitability measured using return on equity, return on assets and net profit margin in 2015-2020 was categorized as good. The results of trend analysis on the current ratio, quick ratio, total debt to equity ratio, total debt to total asset ratio, return on equity, return on assets and net profit margin in 2015-2020 had increased performance. The results of the analysis on the balance sheet and the remaining operating results tend to decrease in financial developments.